Indentifikasi Segmentasi Produk, Demografi, Psikografis dan Dampaknya pada Keputusan Pembelian - Farida Sartika; Luluh Abdillah (Asosiasi Ahli Administrasi Indonesia, 2020)
Human daily needs are never separated from the consideration of their fulfillment. The basis for these considerations differs from one another based on needs, quality, price, prestige, place of purchase, and whether or not the item is well-known. The aims of this study are to determine the effect of demographic and psychographic factors on consumer purchasing decisions and to uncover the right combination of marketing strategies for target segments and target markets for retailers. The psychographic profile of the target addressed is also needed by business people. This factor will provide data such as motives, attitudes, and interests that affect the lifestyle and personality of humans. The result of the study shows that the demographic segmentation variable (X1) has a regression coefficient of 0.323 (positive sign) to the purchase decision (Y) and the calculated t value = 4.577, while psychographic segmentation variable (X2) has a regression coefficient of 0.285 (positive sign) to the purchase decision (Y) t value = 3,560. Adjusted R square value can be seen that the coefficient of determination (R2) obtained is 0.743. This means that for Lux, Dove and Dettol brand soap products, 74.3% of purchasing decisions are influenced by demographic and psychographic segmentation, while the rest is influenced by other variables not examined in this study.